Online Impulsive Buying Behaviour: A Systematic Review - Shailendra Kumar; Ajay Poudyal; Akash Chaurasia (Colombo Business Journal)
The study aims to identify influential factors affecting online impulsive buying behaviour through a systematic review following PRISMA guidelines. A total of 29 studies addressing online impulsive buying behaviour were included. The findings indicate that the majority of studies on online impulsive buying have originated in the Asian region. The influential factors identified were categorised as external (including Web Atmospherics, Online promotions, Electronic Word of Mouth, Advertisements, and CSR activities) and internal factors (comprising Cognitive and Emotional aspects). Additionally, certain moderating factors, such as Demographics and Personality, were also identified. The study suggested directions for future research, encompassing a greater focus on internal factors, including the role of negative emotions in impulsive buying and the impact of scarcity promotional tactics and gamification. These avenues offer valuable pathways for forthcoming research endeavours in this domain.